2013
DOI: 10.1007/s10461-013-0672-0
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ Intentions to Disclose HIV Diagnosis to Children Living with HIV in South Africa: A Theory-Based Approach

Abstract: When people know their HIV serostatus, they can take steps to manage their health and the risk of transmitting HIV to others. Mounting evidence indicates that caregivers often do not disclose to HIV-positive children that the children are living with HIV, but little is known about the modifiable determinants of pediatric HIV disclosure. The present study examined theory-of-planned-behavior predictors of the intention to disclose to children their HIV diagnosis. The participants were 100 caregivers of HIV-posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…D. Bird & Voisin, 2011; Gaskins et al, 2012; Iwelunmor et al, 2014; Rutledge, 2009). Quantitative studies found support for some or all of the individual theory components (Gaskins et al, 2012; Jemmott et al, 2014; Semple et al, 1999; Serovich, Lim, & Mason, 2008). …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…D. Bird & Voisin, 2011; Gaskins et al, 2012; Iwelunmor et al, 2014; Rutledge, 2009). Quantitative studies found support for some or all of the individual theory components (Gaskins et al, 2012; Jemmott et al, 2014; Semple et al, 1999; Serovich, Lim, & Mason, 2008). …”
Section: Resultsmentioning
confidence: 97%
“…Bird, 2009; J. D. Bird & Voisin, 2011; Gaskins et al, 2012; Jemmott et al, 2014; Rutledge, 2007; Semple, Patterson, Shaw, Pedlow, & Grant, 1999; Serovich, 2001). Other individual factors included self-efficacy (Gaskins et al, 2012; Jemmott et al, 2014; Semple et al, 1999), approach/avoidance goals (Chaudoir, Fisher, & Simoni, 2011), normative beliefs (J.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of items, coefficient alpha, and mean (SE) by intervention condition and data-collection period for each theoretical construct are in Table 1. HIV risk-reduction knowledge (Jemmott, Jemmott, Braverman, & Fong, 2005) and its subscales on cultural myths (J. B. Jemmott, 3rd et al, 2013) and condom-use knowledge (Jemmott et al, 2005) are the sum of the correctly answered true-false questions.…”
Section: Methodsmentioning
confidence: 99%